CAUSES AND PREVENTION OF FOOD SAFETY HAZARDS - Natalija ATANASOVA-PANCHEVSKA (ISPEC, 2022)
Safety is an intrinsic quality attribute of foods and it is strictly related to their suitability for human consumption. It is recognised that a main role on food safety is played by microbial contamination and growth of pathogenic microorganisms as well as of presence of microbial/biological toxins that make raw materials and commodities as well as processed foods dangerous and may cause illnesses and infections with main impact on human health. However, food safety is a concept with a wider meaning and do not deals only on the actions to reduce microbial contamination but has to take into account other hazards that during handling, storing and preparing food may determine loss of nutrients making foods of low importance in our diet or cause the formation of unhealthy compounds. Consumers have a right to expect that those who supply the food that they buy have taken every care to manufacture products that will do them no harm. Those with a responsibility for the regulation of the global food industry recognise this principle and legislate accordingly. The three main types of food contaminants are physical, chemical and microbiological. Foods can become contaminated during growing and harvesting of raw materials, storage and transport to the factory and processing into fi nished products. Finished products may then be contaminated during subsequent storage and transport to retail display, as well as during storage and preparation by the consumer. The main vectors of contamination are through contact with surfaces (food contact surfaces and packaging), the air (or other gases), with water (or other liquids) or with people (or animals and insects). Hazards in the raw materials, packaging and the process are controlled by the HACCP plan with additional controls in the quality plan.
Keywords: hazard analysis critical control point (HACCP), hazard, contaminants, food safety